2020
DOI: 10.1177/1087054720914371
|View full text |Cite
|
Sign up to set email alerts
|

Romantic Relationships and Sexual Behavior Among Adolescents With ADHD

Abstract: Objective: Both qualitative and quantitative analyses were used to (a) describe the romantic and sexual relationships of adolescents with ADHD and (b) examine how ADHD-related impairments (e.g., social skill deficits and emotion dysregulation [ED]) are associated with romantic relationship outcomes in this group. Method: Adolescents with ADHD ( N = 171; 80% male; 70% White) responded to questions about their romantic and sexual relationship experiences and ED. Parents provided ratings of ADHD symptoms, ED, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 43 publications
1
5
0
Order By: Relevance
“…However, previous research has also found that risky sexual behaviors are used as a dysfunctional form of emotion regulation in clinical and non-clinical populations ( 69 , 70 ) and our results suggest that this could account for ADHD individuals as well. Furthermore, previous research suggested that risky sexual behaviors as a behavioral expression of emotion regulation appears to be a relevant risk factor for sexual victimization ( 71 , 72 ). In accordance to other previous studies ( 73 75 ), we found a high rate of almost 20% of previous sexually abusive experiences in our ADHD sample, and almost 25% in women with ADHD, showing that this might indeed be a relevant problem which should be addressed in clinical interventions aiming at improving emotion dysregulation.…”
Section: Discussionmentioning
confidence: 99%
“…However, previous research has also found that risky sexual behaviors are used as a dysfunctional form of emotion regulation in clinical and non-clinical populations ( 69 , 70 ) and our results suggest that this could account for ADHD individuals as well. Furthermore, previous research suggested that risky sexual behaviors as a behavioral expression of emotion regulation appears to be a relevant risk factor for sexual victimization ( 71 , 72 ). In accordance to other previous studies ( 73 75 ), we found a high rate of almost 20% of previous sexually abusive experiences in our ADHD sample, and almost 25% in women with ADHD, showing that this might indeed be a relevant problem which should be addressed in clinical interventions aiming at improving emotion dysregulation.…”
Section: Discussionmentioning
confidence: 99%
“…The difficulties with stigma, school, poor social relationships and comorbid mental illness in childhood further increase the risk of social isolation at a time when social integration is key, both to development more generally and to learning social skills that foster healthy relationships later in the life course (Copeland et al., 2018; Umberson et al., 2010). Indeed, by adolescence, ADHD is linked to more risky behavior, higher levels of substance use and (for adolescent girls) higher levels of teen pregnancy (Margherio et al., 2020; Rokeach & Wiener, 2018; Shoham et al., 2019, 2020; Skoglund et al., 2019).…”
Section: Childhood Adhd Stigma and Experiences With Intimate Unions mentioning
confidence: 99%
“…Though prior research has examined ties between ADHD and nonmarital unions (which include both cohabiting and dating relationships), few studies have considered the impact of ADHD on the prevalence, stability and quality of cohabiting unions, specifically (Bruner et al., 2015; Pollock et al., 2017). Yet, positive associations between ADHD and romantic relationship turnover suggest more impulsive entries into intimate unions for those with ADHD, which may lead to a greater number of cohabiting partnerships throughout the life course (Eickmeyer & Manning, 2018; Manning, 2020; Margherio et al., 2020). Similarly, more impulsive entries into cohabiting unions might result in poorer quality unions that are shorter in duration and less likely to end in marriage for those with versus without ADHD (Manning & Cohen, 2012).…”
Section: Opportunities For Future Research On Childhood Adhd and Adulmentioning
confidence: 99%
“…It is characterized by impairing, pervasive inattention and/or impulsivity and hyperactivity that entail a huge burden for the individual and society, including school and work under-achievement, worse physical health (Arrondo et al, 2022; Ruiz-Goikoetxea et al, 2018), and impaired social relations (Harpin, Mazzone, Raynaud, Kahle, & Hodgkins, 2016). Individuals with ADHD struggle with managing conflict and personal relationships and tend to have more tumultuous intimate relationships, with greater number of partners (Margherio et al, 2021), and higher rates of divorce (Klein et al, 2012), compared to neurotypical individuals.…”
Section: Introductionmentioning
confidence: 99%